PENGARUH METODE OUTDOOR LEARNING PADA MATA PELAJARAN IPA DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI 1 PALAKKA - Darsyah, Edi; Nur, Syarif; Asmah Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Outdoor Learning method on improving science learning outcomes among seventh-grade students at SMP Negeri 1 Palakka. The research employed a quantitative approach using a Pre-Experimental Design with a One Group Pretest-Posttest Design. The sample consisted of 30 students from class VII A selected through purposive sampling. Data were collected through observation, tests, and documentation.The results showed that the implementation of the Outdoor Learning method significantly improved students’ science learning outcomes. The average pretest score was 71.50, while the average posttest score increased to 85.50. The normality test using Kolmogorov-Smirnov obtained a significance value of 0.200 (>0.05), indicating that the data were normally distributed. Furthermore, the paired sample t-test produced a significance value of 0.000 (<0.05), indicating a significant difference between pretest and posttest scores. Therefore, the Outdoor Learning method has a positive and significant effect on improving students' science learning outcomes.